Experimental Study of the Electrochemical Impedance Characteristics and Mechanical Properties of High Belite Sulfoaluminate Cement - Niu, Shiwei; Wang, Xingyi; Xing, Jianjian; Li, Jindu; Xie, Ruizhen; Bai, Xiangling; Han, Pengju (International journal of electrochemical science, 2022)
In this paper, a series of electrochemical impedance spectroscopy and compressive strength tests were performed on high belite sulfoaluminate cement with different water-cement ratios. The hydration process of cement materials was analysed according to the generation and development of the impedance curve. Then, the electrochemical impedance spectrum of different hydration times was fitted to obtain electrochemical parameters, and the relationship between electrochemical parameters and mechanical properties was established from the perspective of two electrochemical parameters characterizing pore structure. Furthermore, the influence of different factors on the mechanical properties of cement materials was analysed. The results demonstrated that the water-cement ratio does not change the shape of the Nyquist plot in the cement hydration process. The hydration process can be divided into three stages: early stage, middle stage, and late stage. The porosity decreases with increasing hydration degree, which is manifested as a decrease in the electrochemical parameters α and Q. A novel simple and effective formula is proposed to predict the compressive strength of cement materials considering electrochemical parameters: fcu = A + Blog α - Clog Q. Among the experimental factors, the water-cement ratio is essential to its compressive strength, and the effect of small pores is greater than that of large pores.